Designing Wu Creatives' Brand Activation And Its Promotional Media To Increase Consumer's Brand Awareness - Utomo, Connie Wijaya (Jurnal Vicidi, 2024)
Stress is a problem that is often faced by all kinds of people. Based on a survey conducted by the researcher on 30 Indonesian respondents mostly aged 18-24 years and are currently studying or working, 43.4% of them frequently experience stress, especially at work. Therefore, Wu Creatives developed a DIY stress relief craft kit business idea, where users can release stress through crafting a coaster using jesmonite resin. However, Wu Creatives is still new, so it needs brand awareness from the consumers. Therefore, to increase brand awareness, Wu Creatives designed a brand activation in the form of an online workshop called The Crafting ReLounge targeted for people aged 17 to 27 years along with designing the promotional media distributed through four platforms: Instagram, Tiktok, Tokopedia, and Shopee. This research was designed using qualitative and quantitative data research methods through literature studies from journals and books, interviews with four expert users and four extreme users, and a survey filled out by 57 respondents according to the target market of the Wu Creatives brand. The result of Wu Creatives' brand activation design is the execution of the online workshop itself and the media timeline or the customer journey for its promotional media content. The types of content uploaded by Wu Creatives on social media are multimedia content discussing the product knowledge, tips and tricks, video reels, giveaway, entertainment, promotions, Instagram filters, e-commerce banners, etc